Multiple-input multiple-output passive time reversal acoustic communication using filtered multitone modulation. (April 2017) - Li, Haisen; Sun, Lin; Du, Weidong; Zhou, Tian; Chen, Baowei
Abstract: Passive time reversal (PTR) technique can be exploited to reduce inter-symbol interference (ISI) span and co-channel interference (CCI) span to some extent in the multiple-input multiple-output (MIMO) PTR underwater acoustic communication using single-carrier (SC) modulation. However, there are still large ISI and CCI in the signals processed by PTR if the communication frequency band is relatively wide. The residual ISI and CCI in wideband MIMO PTR communication using SC modulation add to the complexity of the follow-up interference suppression approach. In order to further reduce the span of the residual ISI and CCI, an efficient wideband MIMO-PTR underwater acoustic communication using filtered multitone (FMT) modulation is proposed in this paper. The proposed method is analyzed in theory and verified using the experiment carried out in an experimental pool. The experimental results of the proposed method are compared with that of the MIMO-PTR acoustic communication using SC modulation. The results show that the symbol interval is expanded and the span of residual ISI and CCI is reduced using FMT approach. Compared with the MIMO-PTR acoustic communication using SC modulation, the proposed method possesses higher communication performance and lower computational complexity in channel estimation, PTR, and residual interference suppression.